Influence of left ventricular diastolic dysfunction on results after reconstruction mitral valve surgery in patients with mitral regurgitation - O. F. Luchynets (Ukrainian Journal of Cardiovascular Surgery, 2016)
This research was based on the data of 218 patients with mitral valve regurgitation, who received surgical treatment at National M.M. Amosov Institute of Cardiovascular Surgery National Academy of Medical Sciences of Ukraine from 01.01.2010 to 01.01.2015 years. The average age of patients was 52, 8 ± 13,0 years (16,0-78,0).In postoperative period signs of heart failure (HF) were diagnosed in 43 (19.7%) cases. Hospital mortality was 2.3%. Comparative analysis of clinical data between subgroups of hemodynamically stable patients and patients HF and in postoperative period was performed. Left ventricular(LV) systolic dysfunction in patients with mitral regurgitation(MR) determined the risk of HF in the early postoperative period and adverse outcome. In patients with MR initial decrease of left ventricular ejection fraction(LVEF) to 50% was associated with adverse surgical treatment outcome.